All-solid-state secondary battery and method for manufacturing the same

By using a laminated body structure of a negative electrode active material precursor and a solid electrolyte layer in an all-solid secondary battery, and compressing the positive electrode active material layer after charging, the problem of insufficient battery capacity and energy density is solved, and a high-performance all-solid secondary battery is realized.

CN113748543BActive Publication Date: 2025-03-21FUJIFILM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202080023512.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-27
Filing Date
2020-03-16
Publication Date
2025-03-21
Estimated Expiration
2040-03-16

AI Technical Summary

Technical Problem

In an all-solid secondary battery, it is difficult to fill the solid electrolyte layer into the holes generated in the positive electrode active material layer, resulting in insufficient battery capacity and energy density.

Method used

The battery capacity and energy density of the battery are improved by making a laminate of a positive electrode active material layer and a solid electrolyte layer containing a negative electrode active material precursor, and compressing the positive electrode active material layer after charging.

Benefits of technology

A fully solid-state secondary battery with high battery capacity and high energy density is realized, avoiding the damage of the solid electrolyte layer and the generation of dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113748543B_ABST
    Figure CN113748543B_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing an all-solid-state secondary battery, and an all-solid-state secondary battery manufactured by the manufacturing method. The all-solid-state secondary battery has a solid electrolyte layer containing particles of an inorganic solid electrolyte and a positive electrode active material layer on one surface of the solid electrolyte layer. The manufacturing method of the all-solid-state secondary battery comprises: a process of forming a positive electrode active material layer on one surface of the solid electrolyte layer using a positive electrode composition containing a positive electrode active material and a negative electrode active material precursor; a process of charging a stack including the formed positive electrode active material layer and the solid electrolyte layer; and a process of compressing at least the positive electrode active material layer by applying pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an all-solid-state secondary battery and a manufacturing method thereof. Background Art

[0002] A lithium-ion secondary battery is a storage battery having a negative electrode, a positive electrode, and an electrolyte sandwiched between the negative electrode and the positive electrode, and capable of reciprocating lithium ions between the two electrodes for charge and discharge. In the past, organic electrolytes were used as electrolytes in lithium-ion secondary batteries. However, organic electrolytes are prone to liquid leakage, and short circuits may occur inside the battery due to overcharging and overdischarging, so it is necessary to further improve reliability and safety.

[0003] Under such circumstances, the development of all-solid-state secondary batteries using non-flammable inorganic solid electrolytes instead of organic electrolytes is underway. In all-solid-state secondary batteries, all negative electrodes, electrolytes, and positive electrodes are made of solids, which can greatly improve the safety and reliability of batteries using organic electrolytes, and can also extend their life.

[0004] Generally speaking, secondary batteries that move metal ions back and forth between two electrodes usually have irreversible capacity, and when the battery is charged for the first time after manufacturing, the amount of metal that serves as the metal ion source (the amount of lithium in the case of an all-solid-state lithium-ion secondary battery) decreases (related to the loss of discharge capacity), and sometimes the required battery capacity does not appear.

[0005] As one of the countermeasures for the reduction of the amount of metal caused by the above-mentioned first charge, a technology for supplementing the corresponding metal ions separately from the active material forming the negative electrode active material layer or the positive electrode active material layer can be cited. For example, Patent Document 1 describes a method in which, in a lithium-ion secondary battery using a non-aqueous electrolyte, a voltage is applied to a stack composed of a positive electrode precursor, a negative electrode and a separator comprising a positive electrode active material and a specific lithium compound under specific conditions between the positive electrode precursor and the negative electrode to decompose the lithium compound, thereby pre-doping lithium ions into the negative electrode. In this method, it is described that in addition to the pre-doping of lithium ions, the high-load charge and discharge cycle characteristics of a lithium-ion secondary battery can be optimized by maintaining a non-aqueous electrolyte in the holes generated by the decomposition of the lithium compound.

[0006] Previous technical literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 6251452 Summary of the invention

[0009] Technical issues to be solved by the invention

[0010] However, in all-solid-state secondary batteries, since the electrolyte is also solid, it is difficult to maintain or fill the solid electrolyte layer into the holes generated in the positive electrode active material layer as in Patent Document 1. On the other hand, in order to compensate for the reduction in the amount of metal (the loss of discharge capacity), the more the pre-doping amount of metal ions is increased, the more the energy density will be reduced.

[0011] An object of the present invention is to provide an all-solid-state secondary battery that achieves not only a high battery capacity but also a high energy density, and a method for manufacturing the same.

[0012] Means for solving technical problems

[0013] The present inventors have found that by making a laminate of a positive electrode active material layer containing a negative electrode active material precursor and a solid electrolyte layer, and compressing the positive electrode active material layer after charging the laminate, an all-solid-state secondary battery with higher performance in terms of battery capacity and energy density can be manufactured. The present inventors have further conducted repeated research based on these insights and have completed the present invention.

[0014] That is, the above-mentioned problems were solved by the following means.

[0015] <1> A method for manufacturing an all-solid-state secondary battery, the all-solid-state secondary battery comprising a solid electrolyte layer containing an inorganic solid electrolyte and a positive electrode active material layer on one surface of the solid electrolyte layer, the method comprising:

[0016] A step of forming a positive electrode active material layer on one surface of the solid electrolyte layer using a positive electrode composition containing a positive electrode active material and a negative electrode active material precursor;

[0017] a step of charging a stack including a positive electrode active material layer and a solid electrolyte layer; and

[0018] After the charging step, at least the positive electrode active material layer is compressed by applying pressure.

[0019] <2> The method for producing an all-solid-state secondary battery according to <1>, wherein in the compressing step, the stacked body is pressurized at a pressure of 10 to 1000 MPa.

[0020] <3> The method for producing an all-solid-state secondary battery according to <2>, wherein the pressure is 80 MPa or more.

[0021] <4> The method for producing an all-solid-state secondary battery according to any one of <1> to <3>, wherein the charging step is performed in a state where the stack is pressurized and restrained in a stacking direction.

[0022] <5> The method for producing an all-solid-state secondary battery according to any one of <1> to <4>, wherein the step of compressing the stack is performed without applying a voltage to the stack.

[0023] <6> The method for producing an all-solid-state secondary battery according to any one of <1> to <5>, wherein the negative electrode active material precursor is at least one compound selected from carbonates, oxides and hydroxides of alkali metals or alkaline earth metals.

[0024] <7> The method for producing an all-solid-state secondary battery according to any one of <1> to <6>, wherein the all-solid-state secondary battery has a negative electrode active material layer on the other surface of the solid electrolyte layer.

[0025] <8> The method for producing an all-solid-state secondary battery according to <7>, further comprising, before the charging step, forming a negative electrode active material layer using a negative electrode composition containing silicon or an alloy containing silicon element.

[0026] <9> An all-solid-state secondary battery obtained by the method for producing an all-solid-state secondary battery according to any one of <1> to <8> above.

[0027] Effects of the Invention

[0028] The method for manufacturing an all-solid-state secondary battery according to the present invention can manufacture an all-solid-state secondary battery having high battery capacity and high energy density. The all-solid-state secondary battery of the present invention has high battery capacity and high energy density.

[0029] The above and other features and advantages of the present invention will become more apparent from the following description with appropriate reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a longitudinal sectional view schematically showing a preferred embodiment of the all-solid-state secondary battery of the present invention. DETAILED DESCRIPTION

[0031] In the description of the present invention, a numerical range represented by "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0032] [All-solid-state secondary battery]

[0033] First, an all-solid-state secondary battery manufactured by the method for manufacturing an all-solid-state secondary battery of the present invention (also referred to as the all-solid-state secondary battery of the present invention) will be described.

[0034] The all-solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer between the positive electrode active material layer and the negative electrode active material layer. The all-solid-state secondary battery of the present invention preferably has the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer adjacent to each other.

[0035] In the present invention, unless otherwise specified, the negative electrode active material layer includes not only a preformed negative electrode active material layer (a negative electrode active material layer in a method in which a negative electrode active material layer is preformed) but also a layer of metal precipitated by charging (a negative electrode active material layer in a method in which a negative electrode active material layer is not preformed).

[0036] In the present invention, each layer constituting the all-solid-state secondary battery may have a single-layer structure or a multi-layer structure as long as it exerts a specific function.

[0037] As long as the all-solid-state secondary battery of the present invention has the above-mentioned structure (solid electrolyte layer between the positive electrode active material layer and the negative electrode active material layer), other structures are not particularly limited, and for example, a known structure related to an all-solid-state secondary battery can be adopted.

[0038] Figure 1 The cross-sectional view schematically shows the stacking state of each structural layer constituting the battery in one embodiment of the all-solid-state secondary battery. The all-solid-state secondary battery 10 of this embodiment has a structure in which a negative electrode collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4 and a positive electrode collector 5 are stacked in sequence when viewed from the negative electrode side, and adjacent layers are in direct contact with each other.

[0039] The charge and discharge of the all-solid-state secondary battery of the present invention having such a structure is the same as that of a conventional all-solid-state secondary battery except for pre-doping with metal ions, and will be briefly described below.

[0040] That is, during charging, electrons (e - ) is supplied to the negative electrode side, and at the same time, the alkali metal or alkaline earth metal constituting the positive electrode active material layer is ionized and moves to the negative electrode side through the (conducting) solid electrolyte layer 3, and the ions of the alkali metal or alkaline earth metal are (reduced and) accumulated. For example, in the case of a lithium ion secondary battery, lithium ions (Li + ) is accumulated at the negative electrode.

[0041] And, the details will be described later, when the all-solid-state secondary battery is charged for the first time after manufacturing, the negative electrode active material precursor in the positive electrode active material layer is (oxidatively) decomposed to generate ions of alkali metal or alkaline earth metal (lithium ions in the case of an all-solid-state lithium ion secondary battery), and the ions move to the negative electrode side through the solid electrolyte layer and are replenished (coated). Since the replenishment of the ions is performed before the all-solid-state secondary battery is used, it is also called pre-doping, which is distinguished from the replenishment of ions during use.

[0042] On the one hand, during discharge, the metal ions accumulated in the negative electrode return (move) to the positive electrode side, and the electrons generated in the negative electrode are supplied to the working part 6 and reach the positive electrode. In the example of the all-solid-state secondary battery shown in the figure, a bulb is used in the working part 6, and the bulb is lit by discharge.

[0043] In the all-solid-state secondary battery of the present invention, the negative electrode active material layer can adopt various forms.

[0044] As the method that can be adopted for the negative electrode active material layer, for example, a negative electrode active material layer containing a negative electrode active material described later, a negative electrode active material layer containing a silicon material or a silicon-containing alloy showing a high battery capacity (also referred to as a Si negative electrode), a lithium metal layer, and a method of stacking a solid electrolyte layer and a negative electrode current collector without a negative electrode active material layer (a method of not pre-forming a negative electrode active material layer), etc. The all-solid-state secondary battery of the present invention can appropriately select the method of the negative electrode active material layer according to the required characteristics, manufacturing conditions, etc.

[0045] In an all-solid-state secondary battery in which a negative electrode active material layer is not formed in advance, a portion of the ions of metals belonging to Group 1 of the periodic table (alkali metal ions) or ions of metals belonging to Group 2 of the periodic table (alkaline earth metal ions) accumulated in the negative electrode collector during charging is bonded to electrons, and the negative electrode active material layer is formed by the phenomenon of precipitation as a negative electrode active material (e.g., metal) on the negative electrode collector (including the interface with the solid electrolyte layer or the voids in the solid electrolyte layer). That is, the all-solid-state secondary battery in this manner enables the metal precipitated on the negative electrode collector to function as a negative electrode active material layer. For example, lithium metal has a theoretical capacity of more than 10 times that of graphite, which is commonly used as a negative electrode active material. Therefore, a lithium metal layer can be formed by precipitating lithium metal on the negative electrode collector, and the thickness can be set to be thinner by not pre-forming (stacking) the negative electrode active material layer, and an all-solid-state secondary battery with further improved energy density can be realized.

[0046] Thus, the all-solid-state secondary battery without pre-forming the negative electrode active material layer includes two modes: an uncharged mode (a mode in which the negative electrode active material is not precipitated) and a charged mode (a mode in which the negative electrode active material is precipitated). In addition, in the present invention, the so-called all-solid-state secondary battery without pre-forming the negative electrode active material layer simply means that the negative electrode active material layer is not formed in the layer formation process in the battery manufacturing. As described above, the negative electrode active material layer is formed on the negative electrode collector by charging.

[0047] <Solid electrolyte layer>

[0048] The solid electrolyte layer 3 contains an inorganic solid electrolyte (also referred to as inorganic solid electrolyte particles when in particle form) having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and the components described later within the range not impairing the effects of the present invention, and usually does not contain a positive electrode active material and / or a negative electrode active material.

[0049] The solid electrolyte layer is a layer that exhibits the above-mentioned ion conductivity and functions as a separator that exhibits electronic insulation, and can be applied to solid electrolyte layers that are previously provided in all-solid-state secondary batteries without particular limitation. The solid electrolyte layer can be formed of the above-mentioned inorganic solid electrolyte particles.

[0050] The content of the inorganic solid electrolyte and the like in the solid electrolyte layer is the same as the content in 100% by mass of the solid content of the solid electrolyte composition described later.

[0051] <Positive electrode active material layer>

[0052] The positive electrode active material layer contains an inorganic solid electrolyte having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a positive electrode active material layer, and components described later within the scope of not impairing the effect of the present invention. In addition, in the first uncharged state of the all-solid-state secondary battery, containing a negative electrode active material precursor described later is one of the preferred methods. The inorganic solid electrolyte, positive electrode active material, negative electrode active material precursor, etc. will be described later.

[0053] The contents of the positive electrode active material, the inorganic solid electrolyte, the negative electrode active material precursor, etc. in the positive electrode active material layer are the same as those in 100% by mass of the solid content in the positive electrode composition described later.

[0054] If the positive electrode active material layer contains a negative electrode active material precursor, it is not necessary to use highly active materials (e.g., lithium metal) when manufacturing an all-solid-state secondary battery, and the ions of the metal element can be supplemented (doped), and the battery capacity can be increased. Moreover, by compressing the positive electrode active material layer after the decomposition reaction (flattening the gaps generated by decomposition), the positive electrode active material layer can be made thinner and the (volume) energy density of the all-solid-state secondary battery can be increased.

[0055] The positive electrode active material layer containing the negative electrode active material precursor is preferably suitable for the above-mentioned method of not pre-forming the Si negative electrode or the negative electrode active material layer. When the Si negative electrode is used as the negative electrode active material layer, the irreversible capacity of the silicon material or the silicon-containing alloy is large, and the reduction in capacity (the amount of movable lithium ions) caused by the first charge becomes larger. Moreover, in the method of not pre-forming the negative electrode active material layer, the reduction in capacity caused by the first charge becomes larger as with the Si negative electrode. However, in an all-solid-state secondary battery with a Si negative electrode and an all-solid-state secondary battery in a method of not pre-forming the negative electrode active material layer, by making the positive electrode active material layer contain a negative electrode active material precursor and performing a decomposition reaction during the first charge, the reduced metal ions can be replenished (the metal ions are encapsulated in the Si negative electrode). Furthermore, if the positive electrode active material layer contains a negative electrode active material precursor, the voids generated by the decomposition reaction of the negative electrode active material precursor in the positive electrode active material layer can be used to eliminate the expansion caused by metal ion inclusion during charging or the expansion caused by metal precipitation (volume expansion of the negative electrode active material layer), thereby preventing the destruction of the solid electrolyte layer and inhibiting dendrites from reaching the positive electrode (generating a short circuit). Furthermore, by flattening the voids, the energy density can be increased.

[0056] <Negative electrode active material layer>

[0057] As described above, the negative electrode active material layer uses an inorganic solid electrolyte containing a negative electrode active material, an ion conductive metal belonging to Group 1 or Group 2 of the periodic table as required, and a layer containing the components described later, a lithium metal layer, etc. The inorganic solid electrolyte, the negative electrode active material, etc. will be described later.

[0058] The lithium metal layer that can constitute the negative electrode active material layer refers to a layer of lithium metal, and specifically includes a layer formed by depositing or molding lithium powder, a lithium foil, a lithium vapor-deposited film, and the like.

[0059] In the present invention, from the viewpoint of small volume expansion and volume contraction caused by charge and discharge, the negative electrode active material layer is preferably a negative electrode active material layer comprising a carbonaceous material. On the other hand, from the viewpoint of battery capacity, it is preferred that the negative electrode active material layer is not formed in advance, and from the viewpoint of being able to achieve high battery capacity and effectively prevent the occurrence of short circuits, Si negative electrodes are preferred. If the negative electrode active material layer is a method in which a Si negative electrode or a negative electrode active material layer is not formed in advance, metal ions can be supplemented by the first charge, and the battery capacity and energy density can be improved while taking advantage of the Si negative electrode and the above-mentioned method.

[0060] The contents of the negative electrode active material, the inorganic solid electrolyte, etc. in the negative electrode active material layer are the same as those in 100% by mass of the solid content in the negative electrode composition described later.

[0061] <Thickness of negative electrode active material layer, solid electrolyte layer, and positive electrode active material layer>

[0062] The thickness of the negative electrode active material layer, the solid electrolyte layer, and the positive electrode active material layer are not particularly limited. The thickness of each layer is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm. Since the thickness of the negative electrode active material layer in the method of not forming the negative electrode active material layer in advance varies according to the amount of metal precipitated by charging, it cannot be uniquely determined. In an all-solid-state secondary battery, it is further preferred that the thickness of at least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is 50 μm or more and less than 500 μm. When a lithium metal layer is used as the negative electrode active material layer, the thickness of the lithium metal layer is independent of the above-mentioned thickness of the negative electrode active material layer, and can be set to 0.01 to 100 μm, for example.

[0063] <Current Collector>

[0064] The positive electrode current collector 5 and the negative electrode current collector 1 are preferably electron conductors.

[0065] In the present invention, either the positive electrode current collector or the negative electrode current collector, or both of them, may be simply referred to as a current collector.

[0066] As the material forming the positive electrode collector, in addition to aluminum, aluminum alloy, stainless steel, nickel and titanium, it is preferred to treat the surface of aluminum or stainless steel with carbon, nickel, titanium or silver (forming a thin film), among which aluminum and aluminum alloy are more preferred.

[0067] As the material for forming the negative electrode collector, in addition to aluminum, copper, copper alloys, stainless steel, nickel and titanium, it is preferred to use a material in which the surface of aluminum, copper, copper alloys or stainless steel is treated with carbon, nickel, titanium or silver, and aluminum, copper, copper alloys and stainless steel are more preferred.

[0068] The shape of the current collector is generally a film-like shape, but a mesh, a perforated body, a lath body, a porous body, a foamed body, a molded body of a fiber group, or the like may also be used.

[0069] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm.

[0070] The surface of the current collector is preferably formed with irregularities by surface treatment.

[0071] In the present invention, functional layers or components may be appropriately inserted or arranged between or outside the negative electrode collector, the negative electrode active material layer, the solid electrolyte layer, the positive electrode active material layer, and the positive electrode collector. Furthermore, each layer may be configured as a single layer or a multilayer.

[0072] <Housing>

[0073] The all-solid-state secondary battery manufactured by the manufacturing method of the all-solid-state secondary battery of the present invention can be used as an all-solid-state secondary battery in the state of the above structure according to the purpose, but in order to make it into a form such as a dry cell, it is preferably further enclosed in an appropriate shell for use. The shell can be a metallic shell or a resin (plastic) shell. When a metallic shell is used, for example, shells made of aluminum alloy and stainless steel can be listed. Preferably, the metallic shell is divided into a positive electrode side shell and a negative electrode side shell and is electrically connected to the positive electrode collector and the negative electrode collector, respectively. Preferably, the shell on the positive electrode side and the shell on the negative electrode side are joined and integrated via a short-circuit prevention gasket.

[0074] The all-solid-state secondary battery manufactured by the manufacturing method of the present invention exhibits high battery capacity and high (volume) energy density. That is, the all-solid-state secondary battery of the present invention pre-dopes metal ions into the negative electrode active material layer by the first charge, and even if it has a negative electrode active material layer formed by using a silicon material or a silicon-containing alloy with a large irreversible capacity as the negative electrode active material, and in a method where the negative electrode active material layer is not formed in advance, it also exerts sufficient battery characteristics. In addition, since it has a positive electrode active material layer whose gaps are flattened by the first charge, and the volume is smaller than before the first charge, it shows a high energy density.

[0075] Furthermore, even if the structural layer of the all-solid-state secondary battery is formed of solid particles and the (fast) charge and discharge of the all-solid-state secondary battery is repeated, the generation of short circuits can be suppressed. Even if a layer composed of graphite and a lithium metal layer are used as the negative electrode active material layer, the generation of short circuits can be suppressed.

[0076] The all-solid-state secondary battery of the present invention showing the above-mentioned excellent characteristics is preferably used in a state of pressure constraint in the stacking direction of the structural layer (the overlap direction of the structural layer, usually the thickness direction of the structural layer). Thus, even if the amount of negative electrode active material decreases during discharge, the contact between the solid electrolyte layer and the negative electrode active material is maintained, especially in the manner in which the metal precipitated on the negative electrode collector as the negative electrode active material layer plays a role, because the deactivation amount of the metal caused by charging and discharging (isolated metal amount) can be reduced, the reduction of the battery capacity caused by charging and discharging is suppressed, and excellent cycle characteristics are also shown.

[0077] <Applications of all-solid-state secondary batteries>

[0078] The all-solid-state secondary battery of the present invention can be applied to a variety of purposes. The applicable mode is not particularly limited. For example, when it is mounted on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone handset, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a camcorder, a liquid crystal television, a portable vacuum cleaner, a portable CD, a small disk, an electric shaver, a transceiver, an electronic notepad, a calculator, a portable recorder, a radio, a backup power supply, and a memory card can be listed. As other civilian products, automobiles (electric cars, etc.), electric cars, motors, lighting fixtures, toys, game consoles, load regulators, clocks, flashlights, cameras, and medical equipment (pacemakers, hearing aids, and shoulder massagers, etc.) can be listed. Moreover, it can be used as various military products and aviation products. Moreover, it can also be combined with solar cells.

[0079] [Method for producing all-solid-state secondary battery of the present invention]

[0080] Next, a method for producing an all-solid-state secondary battery of the present invention (also referred to as a production method of the present invention) will be described.

[0081] The production method of the present invention sequentially performs the following steps.

[0082] (Positive electrode active material layer) forming step: a step of forming a positive electrode active material layer on one surface of a solid electrolyte layer (laminated) using a positive electrode composition containing a positive electrode active material and a negative electrode active material precursor

[0083] Step of charging the laminated body: Step of charging the laminated body including the positive electrode active material layer and the solid electrolyte layer

[0084] (Positive electrode active material layer) compression step: After the charging step, at least the positive electrode active material layer is compressed by applying pressure.

[0085] The production method of the present invention preferably further includes the following forming step.

[0086] (Solid electrolyte layer) forming step: a step of forming a solid electrolyte layer using a solid electrolyte composition containing a solid electrolyte

[0087] This forming step can be performed before or after the step of forming the positive electrode active material layer and the step of forming the negative electrode active material layer described below. In each forming step, the order of implementation can be appropriately determined according to the form and formation method of each layer to be formed.

[0088] The production method of the present invention may include the following discharge step.

[0089] Step of discharging the laminate: Step of discharging the laminate

[0090] In the production method of the present invention, the step of discharging may or may not be included after the step of compressing. Preferably, the step of discharging does not exist before the step of compressing.

[0091] When the all-solid-state secondary battery is a battery in which the negative electrode active material layer is formed in advance, the production method of the present invention preferably further comprises the following forming step.

[0092] (Negative electrode active material layer) forming step: a step of forming a negative electrode active material layer using a negative electrode active material, preferably a carbonaceous material as a negative electrode active material, or a negative electrode composition containing silicon or an alloy containing silicon element

[0093] This forming step is preferably performed before the charging step.

[0094] In the present invention, "conducting processes sequentially" refers to the order in which a certain process and another process are performed, and also includes a method of performing another process (including stopping a process) between a certain process and another process. Furthermore, the method of sequentially performing a certain process and another process also includes a method of performing the process by appropriately changing the time, place or implementer.

[0095] In the manufacturing method of the present invention, a solid electrolyte layer, a positive electrode active material layer and a negative electrode active material layer are formed respectively. Each layer can be formed separately, as a laminate, or two or more layers can be formed together or in sequence. Each layer is usually formed in a sheet or plate shape, and can be provided with a substrate, other layers, etc.

[0096] As a substrate, as long as it is a substrate that can support the solid electrolyte layer, there is no particular limitation, and the sheet-like body (plate-like body) of the material described in the above-mentioned collector, organic material, inorganic material, etc. can be listed. As an organic material, various polymers can be listed, specifically, polyethylene terephthalate, polypropylene, polyethylene, cellulose, etc. can be listed. As an inorganic material, for example, glass and ceramics can be listed.

[0097] Examples of other layers include a protective layer (release sheet), a current collector, a coating layer, etc. The solid electrolyte layer used in the embodiment where the negative electrode active material layer is not formed in advance preferably has a negative electrode current collector on its surface.

[0098] In the present invention, a sheet including a solid electrolyte layer and not having a positive electrode active material layer and a negative electrode active material layer is called a solid electrolyte sheet, a sheet including a negative electrode active material layer is called a negative electrode sheet, and a sheet including a positive electrode active material layer is called a positive electrode sheet.

[0099] The thickness of each layer is the same as the thickness of each layer described in the all-solid-state secondary battery of the present invention.

[0100] When manufacturing an all-solid-state secondary battery, a solid electrolyte layer, a positive electrode active material layer, and a negative electrode active material layer in the case where the all-solid-state secondary battery has a negative electrode active material layer in advance are formed (prepared).

[0101] <Step of forming a solid electrolyte layer>

[0102] When this step is carried out, a solid electrolyte composition is prepared.

[0103] The solid electrolyte composition contains an inorganic solid electrolyte, and further contains a binder, a dispersion medium, a conductive auxiliary agent described below, and other components as appropriate.

[0104] The solid electrolyte composition is preferably a non-aqueous composition. In the present invention, the non-aqueous composition refers to a mode in which, in addition to not containing water, a water content (also referred to as water content) is less than 200 ppm. The water content of the solid electrolyte layer is preferably less than 150 ppm, more preferably less than 100 ppm, and further preferably less than 50 ppm. The water content represents the amount of water contained in the solid electrolyte composition (relative to the mass ratio of the solid electrolyte composition). The water content can be obtained by filtering the solid electrolyte composition with a 0.45 μm membrane filter and by Karl Fischer titration.

[0105] Hereinafter, components contained in the solid electrolyte composition and components that may be contained are described.

[0106] -Inorganic solid electrolyte-

[0107] In the present invention, an inorganic solid electrolyte refers to an inorganic solid electrolyte, and a solid electrolyte refers to a solid electrolyte that allows ions to move inside it. Since it does not contain organic matter as the main ion conductive material, it is clearly distinguished from an organic solid electrolyte (a polymer electrolyte represented by polyethylene oxide (PEO) and an organic electrolyte salt represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)). In addition, since the inorganic solid electrolyte is solid in a stable state, it usually does not dissociate or free into cations and anions. In this regard, the inorganic electrolyte salt (LiPF 6 , LiBF 4 , LiFSI, LiCl, etc. There are no particular restrictions as long as the inorganic solid electrolyte has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, but it usually does not have electronic conductivity.

[0108] The inorganic solid electrolyte has the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. The inorganic solid electrolyte can be appropriately selected from a solid electrolyte material suitable for use in such a product. As inorganic solid electrolytes, (i) sulfide inorganic solid electrolytes, (ii) oxide inorganic solid electrolytes, (iii) halide inorganic solid electrolytes and (iv) hydride inorganic solid electrolytes can be listed. From the perspective of high ionic conductivity and easy bonding between particle interfaces, sulfide inorganic solid electrolytes are preferred. In the present invention, the inorganic solid electrolyte can be appropriately selected from an inorganic solid electrolyte material suitable for use in such a product.

[0109] When the all-solid-state secondary battery of the present invention is an all-solid-state lithium-ion secondary battery, the inorganic solid electrolyte preferably has ion conductivity of lithium ions.

[0110] (i) Sulfide-based inorganic solid electrolytes

[0111] The sulfide-based inorganic solid electrolyte contains sulfur atoms and has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and is preferably a compound having electronic insulation. The sulfide-based inorganic solid electrolyte preferably contains at least Li, S, and P as elements and has lithium ion conductivity, but may contain other elements in addition to Li, S, and P depending on the purpose or situation.

[0112] Examples of the sulfide-based inorganic solid electrolyte include lithium ion conductive sulfide-based inorganic solid electrolytes satisfying a composition represented by the following formula (I).

[0113] L a1 M b1 P c1 S d1 A e1 Formula (I)

[0114] In the formula, L represents an element selected from Li, Na and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al and Ge. A represents an element selected from I, Br, Cl and F. a1 to e1 represent the composition ratio of each element, and a1:b1:c1:d1:e1 satisfies 1 to 12:0 to 5:1:2 to 12:0 to 10. a1 is preferably 1 to 9, more preferably 1.5 to 7.5. b1 is preferably 0 to 3, more preferably 0 to 1. d1 is preferably 2.5 to 10, more preferably 3.0 to 8.5. e1 is preferably 0 to 5, more preferably 0 to 3.

[0115] As described below, the composition ratio of each element can be controlled by adjusting the compounding ratio of the raw material compounds when producing the sulfide-based inorganic solid electrolyte.

[0116] The sulfide-based inorganic solid electrolyte may be amorphous (glass), crystallized (glass ceramic), or only partially crystallized. For example, Li-PS-based glass containing Li, P, and S, or Li-PS-based glass ceramic containing Li, P, and S can be used.

[0117] Sulfide-based inorganic solid electrolytes can be made of, for example, lithium sulfide (Li 2 S), phosphorus sulfides (e.g., phosphorus pentasulfide (P 2 S 5 )), phosphorus, sulfur, sodium sulfide, hydrogen sulfide, lithium halide (e.g., LiI, LiBr, LiCl) and sulfide of the element represented by M (e.g., SiS 2 、SnS、GeS 2 ) by reacting at least two or more raw materials.

[0118] Li-PS glass and Li-PS glass ceramics 2 S and P 2 S 5 The ratio of Li 2 S:P 2 S 5 The molar ratio of Li is preferably 60:40 to 90:10, more preferably 68:32 to 78:22. 2 S and P 2 S 5 The ratio of is within this range, and the lithium ion conductivity can be improved. Specifically, the lithium ion conductivity can be preferably set to 1×10 -4 S / cm or more, more preferably 1×10 -3 S / cm or more. There is no particular upper limit, but in practice it is 1×10 -1 S / cm or less.

[0119] As specific examples of sulfide-based inorganic solid electrolytes, combinations of raw materials are shown below. For example, Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -H 2 S. Li 2 SP 2 S 5 -H 2 S-LiCl, Li 2 S-LiI-P2 S 5 、Li 2 S-LiI-Li 2 OP 2 S 5 、Li 2 S-LiBr-P 2 S 5 、Li 2 S-Li 2 OP 2 S 5 、Li 2 S-Li 3 PO 4 -P 2 S 5 、Li 2 SP 2 S 5 -P 2 About 5 、Li 2 SP 2 S 5 -SiS 2 、Li 2 SP 2 S 5 -SiS 2 -LiCl、Li 2 SP 2 S 5 -SnS、Li 2 SP 2 S 5 -Al 2 S 3 、Li 2 S-GeS 2 、Li 2 S-GeS 2 -ZnS、Li 2 S-Ga 2 S 3 、Li 2 S-GeS 2 -Ga 2 S 3 、Li 2 S-GeS 2 -P 2 S 5 、Li 2 S-GeS 2 -Sb 2 S 5 、Li 2 S-GeS 2 -Al 2 S 3 、Li2 S-SiS 2 , Li 2 S-Al 2 S 3 , Li 2 S-SiS 2 -Al 2 S 3 , Li 2 S-SiS 2 -P 2 S 5 , Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -Li 4 SiO 4 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 10 G 2 S 12 etc. Among them, the mixing ratio of each raw material is not limited. As a method for synthesizing a sulfide-based inorganic solid electrolyte material using such a raw material composition, for example, an amorphization method can be cited. As an amorphization method, for example, a mechanical grinding method, a solution method, and a melt quenching method can be cited. This is because it can be processed at room temperature, thereby simplifying the manufacturing process.

[0120] (ii) Oxide-based inorganic solid electrolytes

[0121] The oxide-based inorganic solid electrolyte is preferably a compound that contains oxygen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.

[0122] The ion conductivity of the oxide-based inorganic solid electrolyte is preferably 1×10 -6 S / cm or more, more preferably 5×10 -6 S / cm or more, particularly preferably 1×10 -5 S / cm or more. The upper limit is not particularly limited, but is actually 1×10 - 1 S / cm or less.

[0123] As specific examples of compounds, for example, Li xa La ya TiO3 [xa=0.3~0.7, ya=0.3~0.7] (LLT), Li xb La yb Zr zb M bb mb O nb (M bb is at least one element selected from the group consisting of Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20. ), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, xc satisfies 0<xc≤5, yc satisfies 0<yc≤1, zc satisfies 0<zc≤1, and nc satisfies 0<nc≤6. ), Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (where 1≤xd≤3, 0≤yd≤1, 0≤zd≤2, 0≤ad≤1, 1≤md≤7, 3≤nd≤13), Li (3-2xe) M ee xe D ee O(xe represents a number greater than or equal to 0 and less than or equal to 0.1, M ee Represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. ), Li xf Si yf O zf (1≤xf≤5, 0<yf≤3, 1≤zf≤10), Li xg S yg O zg (1≤xg≤3, 0<yg≤2, 1≤zg≤10), Li 3 BO 3 -Li 2 SO 4 , Li 2 OB 2 O 3 -P 2 O 5 , Li 2 O-SiO 2 , Li6 BaLa 2 Ta 2 O 12 , Li 3 PO (4-3 / 2w) N w (w satisfies w<1), Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zn 0.25 GeO 4 , La with a perovskite crystal structure 0.55 Li 0.35 TiO 3 、LiTi with NASICON (Natrium super ionic conductor) type crystal structure 2 P 3 O 12 , Li 1+xh+yh (Al, Ga) xh (Ti, Ge) 2-xh Si yh P 3-yh O 12 (where 0≤xh≤1, 0≤yh≤1) and Li with a garnet-type crystal structure 7 La 3 Zr 2 O 12 (LLZ) etc. Furthermore, phosphorus compounds containing Li, P and O are also preferred. For example, lithium phosphate (Li 3 PO 4 ), LiPON and LiPOD in which part of the oxygen in lithium phosphate is replaced by nitrogen 1 (D 1 is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C and Ga, etc.

[0124] (iii) Halide-based inorganic solid electrolytes

[0125] The halide-based inorganic solid electrolyte is preferably a compound containing a halogen atom, having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electron insulating properties.

[0126] The halide inorganic solid electrolyte is not particularly limited, and examples thereof include LiCl, LiBr, LiI, and Li described in ADVANCED MATERIALS, 2018, 30, 1803075. 3 Yb 6 , Li 3 YC 6 Among them, Li 3 Yb 6 , Li 3 YC 6 .

[0127] (iv) Hydride-based inorganic solid electrolytes

[0128] The hydride-based inorganic solid electrolyte is preferably a compound that contains hydrogen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.

[0129] The hydride-based inorganic solid electrolyte is not particularly limited, and examples thereof include LiBH 4 , Li 4 (BH 4 ) 3 I. 3LiBH 4 -LiCl, etc.

[0130] The inorganic solid electrolyte is preferably a particle. At this time, the particle size (volume average particle size) of the inorganic solid electrolyte is not particularly limited, preferably 0.01 μm or more, more preferably 0.1 μm or more. As an upper limit, it is preferably 100 μm or less, more preferably 50 μm or less. The particle size of the inorganic solid electrolyte is determined according to the following steps. In a 20 mL sample bottle, the inorganic solid electrolyte particles are diluted with water (heptane in the case of a substance unstable to water) to prepare a 1% dispersion. The diluted dispersion sample is irradiated with 1 kHz ultrasound for 10 minutes and then used immediately in the test. Using the dispersion sample, a laser diffraction / scattering particle size distribution measuring device LA-920 (trade name, manufactured by HORIBA, Ltd.) is used and a quartz cell for measurement is used at a temperature of 25°C to collect data 50 times to obtain the volume average particle size. Other detailed conditions, etc., are referred to JIS Z8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. For each level, 5 samples were prepared and the average value was adopted.

[0131] The inorganic solid electrolyte may be used alone or in combination of two or more.

[0132] The content of the inorganic solid electrolyte in the solid electrolyte composition is not particularly limited, and from the perspective of dispersibility, reduction of interfacial impedance and adhesion, it is preferably 50% by mass or more in 100% by mass of the solid component, more preferably 70% by mass or more, and particularly preferably 90% by mass or more. As the upper limit, there is no particular limitation, and it can be set to 100% by mass, but from the same viewpoint, it is preferably 99.99% by mass or less, more preferably 99.95% by mass or less, and particularly preferably 99.9% by mass or less.

[0133] In the present invention, the solid component refers to a component that does not disappear by volatilization or evaporation when the solid electrolyte composition is dried at 130° C. for 6 hours under a nitrogen atmosphere at a pressure of 1 mmHg. Typically, it refers to a component other than the dispersion medium described below.

[0134] - Adhesives -

[0135] The solid electrolyte composition may contain a binder for binding solid particles such as an inorganic solid electrolyte.

[0136] As the binder, organic polymers can be cited, and known organic polymers suitable for the manufacture of all-solid-state secondary batteries can be used without particular restrictions. As such an organic polymer, for example, fluorine-containing resins, hydrocarbon thermoplastic resins, acrylic resins, polyurethane resins, polyurea resins, polyamide resins, polyimide resins, polyester resins, polyether resins, polycarbonate resins, cellulose derivative resins, etc. can be cited. The binder is preferably a particle. One type of binder can be used alone, or two or more types can be used. When the solid electrolyte composition includes a binder, the content of the binder in the solid component of the solid electrolyte composition is not particularly limited, for example, preferably 0.1 to 10% by mass, more preferably 1 to 10% by mass, and further preferably 2 to 5% by mass.

[0137] --Dispersion medium-

[0138] The solid electrolyte composition of the present invention preferably further contains a dispersion medium.

[0139] The dispersion medium is a dispersion medium that disperses the components contained in the solid electrolyte composition. In the present invention, the dispersion medium is preferably a non-aqueous dispersion medium that does not contain water, usually selected from an organic solvent. In the present invention, the dispersion medium does not contain water, which means that, in addition to the mode in which the water content is 0% by mass, it also includes a mode of less than 0.1% by mass. Among them, the water content in the solid electrolyte composition is preferably set to within the above range (non-aqueous composition).

[0140] The organic solvent is not particularly limited, and examples thereof include various organic solvents such as alcohol compounds, ether compounds, amide compounds, amine compounds, ketone compounds, aromatic compounds, aliphatic compounds, nitrile compounds, and ester compounds.

[0141] The dispersion medium contained in the solid electrolyte composition may be one kind or two or more kinds.

[0142] The content of the dispersion medium in the solid electrolyte composition is not particularly limited, but is preferably 20 to 80% by mass, more preferably 30 to 70% by mass, and particularly preferably 40 to 60% by mass.

[0143] -Other ingredients-

[0144] The solid electrolyte composition may contain other ingredients.

[0145] There are no particular restrictions on other components, and various additives and the like can be mentioned.

[0146] As the above-mentioned additives, for example, thickeners, cross-linking agents (substances that undergo cross-linking reactions by free radical polymerization, polycondensation or ring-opening polymerization, etc.), polymerization initiators (substances that generate acids or free radicals by heat or light, etc.), defoaming agents, leveling agents, dehydrating agents, antioxidants, etc. can be contained.

[0147] The content of other components in the solid electrolyte composition is not particularly limited and can be appropriately set.

[0148] - Preparation of solid electrolyte composition -

[0149] For example, the solid electrolyte composition can be prepared as, for example, a solid mixture or slurry by mixing an inorganic solid electrolyte, more appropriately, a binder, a dispersion medium, other components, and the like in various commonly used mixers.

[0150] There is no particular limitation on the mixing method, and a known mixer such as a ball mill, a bead mill, or a disc mill can be used. In addition, the mixing conditions are not particularly limited. As a mixing environment, any environment such as atmospheric pressure, dry air (dew point below -20°C), and inert gas (for example, argon, helium, or nitrogen) can be used. Since the inorganic solid electrolyte reacts with water, it is preferably mixed in dry air or inert gas.

[0151] -Formation of solid electrolyte layer-

[0152] The solid electrolyte layer is not particularly limited and can be produced by a molding method of pressure-molding a solid electrolyte composition or a coating and drying method of applying a solid electrolyte composition (slurry) containing a dispersion medium and drying it, preferably followed by pressurization.

[0153] The molding method of the solid electrolyte composition can be any method that can mold the solid electrolyte composition into a layer or film, and various known molding methods can be applied, preferably compression molding (for example, compression molding using a hydraulic cylinder press). The pressure during molding is not particularly limited, and is generally preferably set to a range of 50 to 1500 MPa, more preferably set to a range of 150 to 600 MPa, and further preferably set to a range of 100 to 300 MPa. The molding (pressing) time can be a short time (for example, within a few hours) or a long time (more than 1 day).

[0154] The solid electrolyte composition may be heated while being pressurized. In the present invention, preforming is preferably performed without heating, for example, preferably at an ambient temperature of 10 to 50° C. The molding environment is preferably dry air or an inert gas.

[0155] Examples of the coating method of the solid electrolyte composition (slurry) include wet coating methods such as spin coating, dip coating, slit coating, stripe coating, and bar coating. The drying temperature is not particularly limited, but is preferably 30 to 300°C, more preferably 60 to 250°C.

[0156] The applied dried layer of the solid electrolyte composition is preferably pressurized. There are no particular restrictions on the pressurization method and pressure, and for example, the same method and pressure as the molding method and pressure of the solid electrolyte composition can be appropriately adopted. For example, the pressurization can also be performed after laminating the active material layer, etc.

[0157] <Step of forming negative electrode active material layer>

[0158] When the all-solid-state secondary battery is a battery in which the negative electrode active material layer is formed in advance, the production method of the present invention includes a step of forming the negative electrode active material layer.

[0159] When this step is carried out, a negative electrode composition is prepared.

[0160] The negative electrode composition contains a negative electrode active material, preferably an inorganic solid electrolyte, a conductive aid, and further contains a binder, a dispersion medium, a lithium salt, and other components as appropriate. The negative electrode composition may be the negative electrode active material itself, and is preferably a non-aqueous composition.

[0161] The inorganic solid electrolyte, binder, dispersion medium and other components that can be used in the negative electrode composition are as described above. As the lithium salt, any lithium salt used in all-solid-state secondary batteries can be used without particular limitation.

[0162] - Negative electrode active material -

[0163] The negative electrode active material used in the present invention is a material that can embed and release ions of metal elements belonging to Group 1 or Group 2 of the periodic table. The negative electrode active material is preferably a negative electrode active material that can reversibly embed and release lithium ions. There is no particular limitation on the material as long as it has the above-mentioned characteristics, and examples include carbonaceous materials, oxides of metal or semi-metal elements (including composite oxides), lithium monomers, lithium alloys, or negative electrode active materials that can be alloyed with lithium (forming an alloy with lithium). Among them, from the perspective of reliability, carbonaceous materials, oxides of semi-metal elements, metal composite oxides or lithium monomers are preferred. From the perspective of being able to increase the capacity of an all-solid-state secondary battery, negative electrode active materials that can be alloyed with lithium are preferred.

[0164] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon. For example, carbon black such as petroleum pitch, acetylene black (AB), graphite (natural graphite, artificial graphite such as vapor-grown graphite, etc.), and various synthetic resins such as PAN (polyacrylonitrile) resin or furfuryl alcohol resin can be calcined to form a carbonaceous material. PAN carbon fiber, cellulose carbon fiber, pitch carbon fiber, vapor-grown carbon fiber, dehydrated PVA (polyvinyl alcohol) carbon fiber, lignin carbon fiber, glassy carbon fiber and activated carbon fiber, various carbon fiber types, mesophase microspheres, graphite whiskers and flat graphite can be further listed.

[0165] These carbonaceous materials can also be divided into difficult graphitization carbonaceous materials (also referred to as hard carbon) and graphite-based carbonaceous materials according to the degree of graphitization. In addition, the carbonaceous material preferably has the surface spacing or density and the size of the crystallite recorded in Japanese Patent Publication No. 62-22066, Japanese Patent Publication No. 2-6856, and Japanese Patent Publication No. 3-45473. Carbonaceous material may not be a single material, and a mixture of natural graphite and artificial graphite recorded in Japanese Patent Publication No. 5-90844, and graphite with a coating layer recorded in Japanese Patent Publication No. 6-4516 can also be used.

[0166] As the carbonaceous material, hard carbon or graphite can be preferably used, and graphite is more preferably used.

[0167] The oxides of metal or semi-metal elements applicable as negative electrode active materials are not particularly limited as long as they are oxides that can occlude and release lithium, and examples thereof include oxides of metal elements (metal oxides), composite oxides of metal elements or composite oxides of metal elements and semi-metal elements (collectively referred to as metal composite oxides), and oxides of semi-metal elements (semi-metal oxides). As these oxides, amorphous oxides are preferred, and chalcogenides that are reaction products of metal elements and elements of Group 16 of the periodic table are further preferred. In the present invention, semi-metal elements refer to elements that exhibit properties between metal elements and non-semi-metal elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and further include three elements of selenium, polonium and astatine. Furthermore, amorphous refers to a material having a broad scattering band having a vertex in the region of 20° to 40° at a 2θ value by an X-ray diffraction method using CuKα rays, and may also have crystalline diffraction lines. The strongest intensity among the crystalline diffraction lines observed at 2θ values ​​of 40° to 70° is preferably 100 times or less, more preferably 5 times or less, the intensity of the diffraction line at the top of the broad scattering band observed at 2θ values ​​of 20° to 40°, and particularly preferably the diffraction line without crystallinity.

[0168] Among the compound groups consisting of the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and (composite) oxides or chalcogenides consisting of a single element or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (for example, Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi) are particularly preferred. Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga 2 O 3 、GeO、PbO、PbO 2 , Pb 2 O 3 , Pb 2 O 4 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 8 Bi 2 O 3 , Sb 2 O 8 Si 2 O 3 , Sb 2 O 5 、Bi 2 O 3 、Bi2 O 4 、GeS、PbS、PbS 2 , Sb 2 S 3 or Sb 2 S 5 .

[0169] Preferred examples of negative electrode active materials that can be used together with the amorphous oxides containing Sn, Si, or Ge as the core include carbonaceous materials that can occlude and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, and negative electrode active materials that can alloy with lithium.

[0170] From the viewpoint of high current density charge and discharge characteristics, it is preferred that the oxide of a metal or semi-metal element, especially the metal (composite) oxide and the above-mentioned chalcogenide contain at least one of titanium and lithium as a constituent component. As the metal composite oxide containing lithium (lithium composite metal oxide), for example, composite oxides of lithium oxide and the above-mentioned metal (composite) oxide or the above-mentioned chalcogenide can be listed, and more specifically, Li 2 SnO 2 .

[0171] The negative electrode active material, such as a metal oxide, preferably contains titanium (titanium oxide). 4 Ti 5 O 12 (Lithium titanate [LTO]) has a small volume change when storing and releasing lithium ions, and therefore has excellent rapid charge and discharge characteristics, and can suppress electrode degradation and increase the life of the lithium ion secondary battery, and is therefore preferred from this point of view.

[0172] The lithium alloy used as the negative electrode active material is not particularly limited as long as it is an alloy commonly used as a negative electrode active material for secondary batteries, and examples thereof include lithium aluminum alloys.

[0173] The negative electrode active material that can form an alloy with lithium is not particularly limited as long as it is a material commonly used as a negative electrode active material for a secondary battery. The expansion and contraction of this active material caused by the charging and discharging of the all-solid-state secondary battery become larger. As the above-mentioned active material, negative electrode active materials (alloys) having silicon or tin elements, various metals such as Al and In can be listed, preferably negative electrode active materials (active materials containing silicon elements) having silicon elements that can achieve higher battery capacity, more preferably active materials containing silicon elements having a silicon content of more than 50 mol% of all constituent elements.

[0174] Generally speaking, the negative electrode containing these negative electrode active materials (Si negative electrode containing active materials containing silicon elements, Sn negative electrode containing active materials containing tin elements, etc.) can contain more Li ions compared with carbon negative electrodes (graphite and acetylene black, etc.). That is, the amount of Li ions contained per unit mass increases. Therefore, the battery capacity can be increased. As a result, it has the advantage of being able to extend the battery driving time.

[0175] Examples of active materials containing silicon include silicon materials such as Si and SiOx (0<x≤1), and silicon-containing alloys containing titanium, vanadium, chromium, manganese, nickel, copper, lanthanum, etc. (e.g., LaSi 2 、VSi 2 , La-Si, Gd-Si, Ni-Si) or organized active materials (e.g., LaSi 2 / Si) and also contains SnSiO 3 SnSiS 3 Active materials of silicon and tin, etc. In addition, SiOx can be used as a negative electrode active material (semi-metallic oxide) by itself, and since Si is generated by the operation of the all-solid-state secondary battery, it can be used as a negative electrode active material (its precursor material) alloyed with lithium.

[0176] Examples of the negative electrode active material containing tin include Sn, SnO, SnO 2 、SnS、SnS 2 , and further containing the above-mentioned silicon element and tin element active material, etc. In addition, composite oxides with lithium oxide, such as Li 2 SnO 2 .

[0177] In the present invention, the above-mentioned negative electrode active material can be used without particular restrictions. From the viewpoint of battery capacity, as the negative electrode active material, the negative electrode active material that can be alloyed with lithium is preferred, among which the above-mentioned silicon material or silicon-containing alloy (alloy containing silicon element) is more preferred, and silicon (Si) or silicon-containing alloy is further preferred.

[0178] The shape of the negative electrode active material is not particularly limited, and is preferably in the form of particles. The particle size (volume average particle size) of the negative electrode active material is preferably 0.1 to 60 μm. In order to set the specified particle size, a conventional pulverizer or classifier is used. For example, a mortar, a ball mill, a sand mill, a vibrating ball mill, a satellite ball mill, a planetary ball mill, a rotary airflow jet mill, a sieve, etc. can be preferably used. During pulverization, wet pulverization in which water or an organic solvent such as methanol coexists can also be performed. In order to obtain the desired particle size, classification is preferably performed. There is no particular limitation on the classification method, and a sieve, a wind classifier, etc. can be used. Classification can be performed using both dry and wet methods. The average particle size of the negative electrode active material particles can be determined by the same method as the method for determining the volume average particle size of the above-mentioned inorganic solid electrolyte.

[0179] In the present invention, inductively coupled plasma (ICP) emission spectrometry can be used as a measurement method, and as a simple method, the chemical formula of the compound obtained by the calcination method can be calculated from the mass difference of the powder before and after calcination.

[0180] The surface of the negative electrode active material can also be coated with different metal oxides. As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be listed. Specifically, titanate spinel, tantalum oxides, niobium oxides, lithium niobate compounds, etc. can be listed. Specifically, Li 4 Ti 5 O 12 , Li 2 Ti 2 O 5 、LiTaO 3 、LiNbO 3 、LiAlO 2 , Li 2 ZrO 3 , Li 2 WO 4 , Li 2 TiO 3 , Li 2 B 4 O 7 , Li 3 PO 4 , Li 2 MoO 4 , Li 3 BO 3 、LiBO 2 , Li 2 CO 3 , Li 2 SiO 3 、SiO 2 、TiO 2、ZrO 2 、Al 2 O 3 , B 2 O 3 wait.

[0181] Furthermore, the surface of the electrode including the negative electrode active material may be surface-treated with sulfur or phosphorus.

[0182] Furthermore, the surface of the negative electrode active material particles may be subjected to a surface treatment using actinic rays or active gas (plasma, etc.) before and after the above-mentioned surface coating.

[0183] The above-mentioned negative electrode active materials may be used alone or in combination of two or more.

[0184] When forming the negative electrode active material layer, the negative electrode active material layer has a unit area (cm 2 The mass (mg) (weight per unit area) of the negative electrode active material is not particularly limited and can be appropriately determined according to the designed battery capacity.

[0185] -Conductive additives-

[0186] The negative electrode composition preferably further contains a conductive auxiliary agent, and in particular, an active material containing a silicon element as a negative electrode active material is preferably used in combination with a conductive auxiliary agent.

[0187] There are no particular restrictions on the conductive aid, and generally known conductive aids can be used. For example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjenblack, and furnace black, amorphous carbon such as needle coke, carbon fibers such as vapor-grown carbon fibers and carbon nanotubes, carbonaceous materials such as graphene and fullerene, and metal powders and metal fibers such as copper and nickel, or conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives can be used.

[0188] In the present invention, when an active material and a conductive aid are used in combination, among the conductive aids, a conductive aid that does not embed and release Li and does not play the role of an active material when the battery is charged and discharged is used as a conductive aid. Therefore, among the conductive aids, those that can play the role of an active material in the active material layer when the battery is charged and discharged are classified as active materials rather than conductive aids. Whether the active material plays the role when the battery is charged and discharged is determined by the combination with the active material, not solely determined.

[0189] The shape of the conductive auxiliary agent is not particularly limited, but is preferably in the form of particles.

[0190] The conductive auxiliary agent may be used alone or in combination of two or more.

[0191] The content of the negative electrode active material in the negative electrode composition is not particularly limited, but is preferably 100 mass % or less, more preferably 10 to 80 mass %, and further preferably 20 to 80 mass %, based on 100 mass % of the solid content.

[0192] When the negative electrode composition contains an inorganic solid electrolyte, the total content of the inorganic solid electrolyte and the negative electrode active material in the negative electrode composition is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, further preferably 50% by mass or more, particularly preferably 70% by mass or more, and most preferably 90% by mass or more. As the upper limit, it is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and particularly preferably 99% by mass or less.

[0193] The content of the conductive aid in the negative electrode composition is preferably 0.1 to 20% by mass, more preferably 0.5 to 10% by mass, based on 100% by mass of the solid content.

[0194] The contents of the binder and the dispersion medium in the negative electrode composition are not particularly limited, and can be, for example, the above-mentioned contents in the solid electrolyte composition.

[0195] Furthermore, the contents of the lithium salt and other components in the negative electrode composition are not particularly limited and can be appropriately set, for example, to the above-mentioned contents in the solid electrolyte composition.

[0196] - Preparation of negative electrode composition -

[0197] The negative electrode composition can be prepared by the same method and conditions as those for preparing the above-mentioned solid electrolyte composition.

[0198] -Formation of negative electrode active material layer-

[0199] The negative electrode active material layer is not particularly limited and can be prepared by the same method and conditions as the formation of the solid electrolyte layer. In the formation of the negative electrode active material layer, the negative electrode composition applied and dried can be heated while being pressurized. The heating temperature is not particularly limited and is generally in the range of 30 to 300°C.

[0200] As a method for forming a negative electrode active material layer on the surface of the solid electrolyte layer on the opposite side (the other) of the positive electrode active material layer, there is no particular limitation, and a common method can be applied. For example, a method of forming a solid electrolyte layer and a negative electrode active material layer and stacking two layers, a method of forming a negative electrode active material layer or a solid electrolyte layer on the surface of a solid electrolyte layer or a negative electrode active material layer can be cited.

[0201] The method of laminating the two layers is not particularly limited, and examples thereof include a method of laminating by pressure bonding, a method of placing a negative electrode active material on the surface of a solid electrolyte layer and applying pressure, and a laminating method.

[0202] There is no particular limitation on the method of compression lamination. For example, there can be cited a method of placing (arranging) a negative electrode active material layer on the surface of a solid electrolyte layer and then pressing it. In the method of compression lamination and the method of pressurizing the negative electrode active material on the surface of a solid electrolyte layer, there is no particular limitation on the method and conditions of compression lamination or pressurization as long as the two layers can be compressed. The pressure can be any pressure that can compress the negative electrode active material layer. For example, it can be set to 1 MPa or more, preferably 1 to 150 MPa, and more preferably 5 to 60 MPa. Compression lamination or pressurization can be performed under heating. In the present invention, it is preferably performed without heating, for example, more preferably at an ambient temperature of 0 to 50°C. The environment for compression lamination or pressurization is the same as the environment when preparing the solid electrolyte composition.

[0203] The lamination method is not particularly limited, and for example, a method in which an electrolyte solution is applied to the surface of the solid electrolyte layer and then the negative electrode active material layer is placed (arranged) is exemplified. The electrolyte solution used is not particularly limited.

[0204] There is no particular limitation on the method of directly forming the negative electrode active material layer or the solid electrolyte layer on the surface of the solid electrolyte layer or the negative electrode active material layer, and for example, a method of coating and drying the negative electrode composition or the solid electrolyte composition on the surface of the solid electrolyte layer or the negative electrode active material layer can be cited. There is no particular limitation on the method and conditions for coating and drying, and for example, the coating and drying method and conditions of the solid electrolyte composition can be applied.

[0205] When the all-solid-state secondary battery is a method in which the negative electrode active material layer is not formed in advance, the negative electrode active material layer is formed by the charging process described later. At this time, a compound (such as a positive electrode active material, etc.) that produces ions of metals belonging to Group 1 or Group 2 of the periodic table is used instead of the above-mentioned negative electrode active material. The negative electrode active material layer can be formed by bonding the ions generated from the compound to the negative electrode collector or its vicinity and precipitating as a metal.

[0206] <Step of forming a positive electrode active material layer>

[0207] When the step of forming the positive electrode active material layer is carried out, a positive electrode composition is prepared.

[0208] The positive electrode composition contains a positive electrode active material and a negative electrode active material precursor, preferably an inorganic solid electrolyte and a conductive aid, and further contains a binder, a dispersion medium, a lithium salt and other components as appropriate. The positive electrode composition is preferably a non-aqueous composition.

[0209] The inorganic solid electrolyte, the conductive aid, the binder, the dispersion medium, the lithium salt, and other components that can be used in the positive electrode composition are as described above.

[0210] - Positive electrode active material -

[0211] The positive electrode active material layer used in the present invention is a material that can absorb and release ions of metal elements belonging to Group 1 or Group 2 of the periodic table. The positive electrode active material layer is preferably a metal oxide (preferably a transition metal oxide).

[0212] The positive electrode active material is preferably a material that can reversibly insert and release lithium ions. As long as the material has the above-mentioned properties, there is no particular limitation, and it can be a transition metal oxide or an organic substance, an element that can be complexed with Li such as sulfur, or a complex of sulfur and metal.

[0213] Among them, as the positive electrode active material, it is preferred to use a transition metal oxide, and more preferably a transition metal element M a (one or more elements selected from Co, Ni, Fe, Mn, Cu and V) transition metal oxide. In addition, the element M may be mixed in the transition metal oxide. b (Metals other than lithium, elements of Group 1 (Ia) of the periodic table, elements of Group 2 (IIa), Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, or B, etc.) As a mixed amount, it is preferably 1:1 relative to the transition metal element M a The amount of Li / M is preferably 0 to 30 mol%. a The components are mixed and synthesized so that the molar ratio of them becomes 0.3 to 2.2.

[0214] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.

[0215] Specific examples of transition metal oxides having a layered rock salt structure (MA) include LiCoO 2(lithium cobalt oxide [LCO]), LiNi 2 O 2 (Lithium Nickel Oxide), LiNi 0.85 Co 0.10 Al 0.05 O 2 (lithium nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O 2 (lithium manganese nickel oxide).

[0216] Specific examples of the transition metal oxide (MB) having a spinel structure include LiMn 2 O 4 (LMO), LiCoMnO 4 , Li 2 FeMn 3 O 8 , Li 2 CuMn 3 O 8 , Li 2 CrMn 3 O 8 Li 2 NiMn 3 O 8 .

[0217] Examples of the lithium-containing transition metal phosphate compound (MC) include LiFePO 4 Li 3 Fe 2 (PO 4 ) 3 Olivine type iron phosphate, LiFeP 2 O 7 Iron pyrophosphate, LiCoPO 4 Cobalt phosphates and Li 3 V 2 (PO 4 ) 3 (lithium vanadium phosphate) and other monoclinic NASICON-type vanadium phosphate salts.

[0218] Examples of the lithium-containing transition metal halophosphate compound (MD) include Li 2 FePO 4 F and other fluoroferric phosphates, Li 2 MnPO 4 F and other manganese fluorophosphates and Li 2CoPO 4 F and other cobalt fluorophosphates.

[0219] Examples of the lithium-containing transition metal silicate compound (ME) include Li 2 FeSiO 4 , Li 2 MnSiO 4 Li 2 CoSiO 4 wait.

[0220] In the present invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.

[0221] The shape of the positive electrode active material is not particularly limited, and is preferably in the form of particles. The volume average particle size (sphere-converted average particle size) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1 to 50 μm. In order to make the positive electrode active material a specified particle size, a conventional pulverizer or classifier can be used. The positive electrode active material obtained by the calcination method can also be used after washing with water, an acidic aqueous solution, an alkaline aqueous solution, and an organic solvent. The average particle size of the positive electrode active material particles can be measured by the same method as the method for measuring the volume average particle size of the above-mentioned inorganic solid electrolyte.

[0222] The surface of the positive electrode active material may be coated with other metal oxides, similarly to the negative electrode active material.

[0223] The above-mentioned positive electrode active materials may be used alone or in combination of two or more.

[0224] When forming the positive electrode active material layer, the positive electrode active material layer has a unit area (cm 2 The mass (mg) (weight per unit area) of the positive electrode active material is not particularly limited and can be appropriately determined according to the designed battery capacity.

[0225] -Negative electrode active material precursor-

[0226] The negative electrode active material precursor is a compound that generates (releases) ions (metal ions) of metal elements belonging to Group 1 or Group 2 of the periodic table in the positive electrode active material layer through the charging process described later. The generated metal ions reach the negative electrode active material layer by charging the all-solid-state secondary battery, etc. to pre-dope the negative electrode active material layer. When the all-solid-state secondary battery is a method in which the negative electrode active material layer is not formed in advance, the metal ions reach the negative electrode collector and bond with the electrons to precipitate as metal, thereby pre-doping the negative electrode active material layer.

[0227] The precursor of the negative electrode active material is not particularly limited as long as it has such characteristics or functions, and compounds containing the above-mentioned metal elements can be listed, but from the perspective of releasing lithium ions and decomposing during the first charge, and not contributing to the release of lithium ions during the next charge, it is different from the lithium salt that is the supporting electrolyte of the material used as the all-solid-state secondary battery. In this way, from the perspective of being unable to reversibly embed and release lithium ions caused by charging and discharging, the precursor of the negative electrode active material is also a compound different from the above-mentioned positive electrode active material.

[0228] The negative electrode active material precursor is preferably an inorganic compound containing the above-mentioned metal element, more preferably an inorganic salt that produces the above-mentioned metal ions and anions, further preferably a carbonate, oxide or hydroxide of the above-mentioned metal element (alkali metal or alkaline earth metal), and particularly preferably a compound selected from carbonate. The inorganic salt is not particularly limited, and is preferably an inorganic salt that produces gas by decomposition at room temperature and pressure, preferably under a charging environment. For example, carbonates produce carbonate ions with ions of metal elements by oxidative decomposition. The ions of the generated metal elements become the constituent materials of the negative electrode active material layer, and the carbonate ions are released (disappeared) from the positive electrode active material layer by changing into carbon dioxide gas. Therefore, carbonates will not remain in the positive electrode active material layer containing the decomposed product, and the battery characteristics (energy density) caused by containing carbonates can be avoided.

[0229] When the all-solid-state secondary battery is an all-solid-state lithium-ion secondary battery, the metal element forming the negative electrode active material precursor is preferably lithium.

[0230] As the precursor of the negative electrode active material, for example, inorganic salts such as carbonates, oxides, hydroxides, halides, and organic salts such as carboxylates (for example, oxalates) of the above-mentioned metal elements can be listed. As a compound (lithium salt) containing the lithium element as a precursor of the negative electrode active material, specifically, for example, lithium carbonate, lithium oxide, lithium hydroxide, lithium fluoride, lithium chloride, lithium oxalate, lithium iodide, lithium nitride, lithium sulfide, lithium phosphide, lithium nitrate, lithium sulfate, lithium phosphate, lithium oxalate, lithium formate, lithium acetate, etc. can be listed, preferably lithium carbonate, lithium oxide or lithium hydroxide, and lithium carbonate is more preferred from the viewpoint of being able to be safely handled in the air (low hygroscopicity).

[0231] The positive electrode composition may contain one type of negative electrode active material precursor, or may contain two or more types.

[0232] The average particle size of the negative electrode active material precursor is not particularly limited, but is preferably 0.01 to 10 μm, and more preferably 0.1 to 1 μm. The average particle size is a value measured in the same manner as the average particle size of the inorganic solid electrolyte particles.

[0233] The content of the positive electrode active material in the positive electrode composition is not particularly limited, but is preferably 10 to 95% by mass, more preferably 30 to 90% by mass, further preferably 50 to 85% by mass, and particularly preferably 55 to 80% by mass based on 100% by mass of the solid content.

[0234] When the positive electrode composition contains an inorganic solid electrolyte, the total content of the inorganic solid electrolyte and the positive electrode active material layer in the positive electrode composition is preferably 5% by mass or more, more preferably 10% by mass or more, more preferably 15% by mass or more, more preferably 50% by mass or more, especially preferably 70% by mass or more, and most preferably 90% by mass or more. As the upper limit, it is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and especially preferably 99% by mass or less.

[0235] Since the content of the negative electrode active material precursor in the positive electrode composition varies according to the amount of metal element ions to be supplemented, it is impossible to determine uniquely, for example, in 100% by mass of the solid content, it is preferably 50% by mass or less, more preferably 5 to 30% by mass, and further preferably 7 to 20% by mass. The total content of the positive electrode active material and the negative electrode active material precursor in the positive electrode composition is not particularly limited, and is preferably 70 to 90% by mass.

[0236] The content of the conductive auxiliary agent in the positive electrode composition is preferably 0.1 to 20% by mass, more preferably 0.5 to 10% by mass, based on 100% by mass of the solid content.

[0237] The contents of the binder and the dispersion medium in the positive electrode composition are not particularly limited, and can be, for example, the above-mentioned contents in the solid electrolyte composition.

[0238] The content of other components in the positive electrode composition is not particularly limited and can be appropriately set. For example, the content described above for the solid electrolyte composition can be set.

[0239] - Preparation of positive electrode composition -

[0240] The positive electrode composition can be prepared by the same method and conditions as those for preparing the above-mentioned solid electrolyte composition.

[0241] -Formation of positive electrode active material layer-

[0242] The positive electrode active material layer is not particularly limited and can be prepared by the same method and conditions as the formation of the above-mentioned solid electrolyte layer. In the process of forming the positive electrode active material layer, it is preferred to heat the positive electrode composition applied and dried while pressurizing. The heating temperature is not particularly limited and is generally in the range of 30 to 300°C.

[0243] As a method for forming a positive electrode active material layer on the surface of the solid electrolyte layer on the opposite side (one of them) of the negative electrode active material layer, there is no particular limitation, and a common method can be applied. For example, a method of forming a solid electrolyte layer and a positive electrode active material layer and stacking two layers, a method of forming a positive electrode active material layer or a solid electrolyte layer on the surface of a solid electrolyte layer or a positive electrode active material layer can be cited.

[0244] As a method for forming a positive electrode active material layer on one surface of a solid electrolyte layer, the same method as the method for forming a negative electrode active material layer on the other surface of a solid electrolyte layer can be cited, except that a positive electrode active material, a positive electrode active material layer or a positive electrode composition is used instead of a negative electrode active material, a negative electrode active material layer or a negative electrode composition.

[0245] The steps of forming the solid electrolyte layer and the positive electrode active material layer are performed as described above to produce a laminate including the positive electrode active material layer and the solid electrolyte layer. Furthermore, when the all-solid-state secondary battery is a method of pre-forming the negative electrode active material layer, the step of forming the negative electrode active material layer is further performed to produce a laminate including the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer.

[0246] The laminate obtained in this manner is an all-solid-state secondary battery before initial charge and compression, and is also referred to as an all-solid-state secondary battery precursor.

[0247] <Step of charging the laminate>

[0248] In the production method of the present invention, the step of charging the obtained laminated body is then performed.

[0249] The charging conditions may be any conditions that allow the negative electrode active material precursor in the positive electrode active material layer to be oxidatively decomposed, and examples thereof include the following conditions.

[0250] Current: 0.05~1mA / cm 2

[0251] Voltage: 4.2~4.5V

[0252] Charging time: 1 to 20 hours

[0253] Temperature: 25~60℃

[0254] Since the anions (generated compounds) of the negative electrode active material precursor are released to the outside of the stack, the charging process is preferably performed in an open state rather than in a sealed state of the stack. The environment at this time is the same as that when the solid electrolyte composition is prepared.

[0255] The charging process is preferably performed by pressurizing the stack in the stacking direction. Thus, it is possible to suppress problems caused by the volume change of the negative electrode active material layer (for example, damage to the solid electrolyte layer). The pressure at this time is not particularly limited, preferably 0.05MPa or more, more preferably 1MPa. The upper limit is the pressure that does not compress the positive electrode active material layer, for example, preferably less than 10MPa, more preferably less than 8MPa.

[0256] In this process, charging may be performed once or multiple times.

[0257] Through the charging process, the negative electrode active material precursor in the positive electrode active material layer is oxidized and decomposed to produce metal ions and anions. The generated metal ions move to the negative electrode active material layer or its vicinity to dope the negative electrode active material layer. On the other hand, the anions sometimes remain in the positive electrode active material layer, but preferably the gas changes and is released to the outside of the stack. In this way, in the manufacturing method of the present invention, pre-doping can be performed safely and simply without using lithium metal or the like.

[0258] When charging is completed in this manner, voids are generated in the positive electrode active material layer due to oxidative decomposition of the negative electrode active material precursor.

[0259] Since the porosity in the positive electrode active material layer after charging (including the porosity of all voids from the negative electrode active material precursor) varies depending on the type or particle size of the positive electrode active material layer, the formation conditions of the positive electrode active material layer, the type, particle size or content of the negative electrode active material precursor, etc., it cannot be uniquely determined. For example, it can be set to 5 to 30%, preferably 15 to 25%.

[0260] The porosity of the positive electrode active material layer is measured by the following method. That is, an arbitrary cross section of the positive electrode active material layer is observed by a scanning electron microscope (SEM), and the obtained SEM photograph is taken at a magnification of 30,000 times, and the area of ​​the void in the field of view 3μm×2.5μm is obtained, and the area is divided by the field of view area (7.5μm 2 ) is used to calculate the value (percentage) obtained.

[0261] In an all-solid-state secondary battery in which a negative electrode active material layer is not formed in advance, a negative electrode current collector that can form a basis for ions of a metal belonging to Group 1 or Group 2 of the periodic table can be appropriately used. Through the charging process, not only a coating caused by the decomposition of the negative electrode active material precursor is formed, but also a negative electrode active material layer is formed.

[0262] <Step of discharging the laminate>

[0263] In the production method of the present invention, a step of discharging the stacked body can also be performed.

[0264] The discharge conditions are not particularly limited, and for example, the following conditions may be mentioned.

[0265] Current: 0.05~1mA / cm 2

[0266] Voltage: 2.5~3.0V

[0267] Charging time: 1 to 20 hours

[0268] Temperature: 25~60℃

[0269] From the viewpoint of being able to release the anions of the negative electrode active material precursor to the outside of the stack, it is preferred to perform the discharge step with the stack open. The environment at this time is the same as that when the solid electrolyte composition is prepared.

[0270] Preferably, the discharge process is performed by pressurizing and constraining the stack in the stacking direction. As a result, the close contact between the collector and the electrode layer can be maintained. The pressure at this time is not particularly limited and can be set to the above-mentioned pressure range in the charging process, which can be the same as or different from the pressure in the charging process.

[0271] In this step, the discharge may be performed once or multiple times.

[0272] Metal ions are generated from the negative electrode active material layer or its vicinity through the discharge process and reach the positive electrode active material layer. However, the metal ions and the positive electrode active material into which the metal ions are further introduced do not completely fill the voids from the negative electrode active material precursor, and the positive electrode active material layer may have voids (residues) that are flattened in the compression process described later.

[0273] The porosity of the positive electrode active material layer after discharge is not particularly limited, and can be, for example, 10% or more, and preferably 20% or more.

[0274] In an all-solid-state secondary battery in which a negative electrode active material layer is not formed in advance, metal precipitated by a discharge process and a charge process is ionized and moves to the positive electrode active material layer (the negative electrode active material layer is reduced in volume or disappears).

[0275] In the present invention, the charging through the above-mentioned charging process is called initial charging, and the discharging through the above-mentioned discharging process is called initial discharging. In addition, the initial charging and initial discharging are collectively referred to as initialization, and initialization can be performed as one cycle of one initial charging and one initial discharging, or multiple cycles.

[0276] <Step of compressing the positive electrode active material layer>

[0277] In the production method of the present invention, the step of pressurizing and compressing the positive electrode active material layer is then performed.

[0278] Through this process, the voids formed in the positive electrode active material layer after charging or the voids remaining in the positive electrode active material layer after discharging are flattened (pressed) and the positive electrode active material layer becomes a thin layer (densified). As a result, the total thickness (volume) of the all-solid-state secondary battery is reduced and the energy density is improved.

[0279] The compression step may be performed as long as at least the positive electrode active material layer can be compressed. When compression of the charged positive electrode active material layer is considered, the positive electrode active material layer is preferably compressed by pressurizing the stacked body as a precursor of the all-solid-state secondary battery.

[0280] There is no particular limitation on the method of compressing the positive electrode active material layer, and various known pressurization methods can be applied, preferably compression (for example, compression using a hydraulic cylinder press). The pressure in this process is not particularly limited as long as it is a pressure that can flatten the voids, and is preferably higher than the pressure constraint in the above-mentioned charging process. The pressure can be appropriately determined according to the type or content of the positive electrode active material layer, the amount of voids, etc., for example, it is preferably set in the range of 10 to 1000 MPa. As the lower limit of the pressure, it is more preferably 40 MPa or more, more preferably 50 MPa or more, particularly preferably 60 MPa or more, and most preferably 80 MPa or more. As the upper limit, it is more preferably 1000 MPa or less, and more preferably 750 MPa or less. There is no particular limitation on the pressing time, and it can be a short time (for example, within a few hours) or a long time (more than 1 day).

[0281] The positive electrode active material layer may be heated at the same time as the compression, but in the present invention, the compression is preferably performed without heating, for example, preferably at an ambient temperature of 10 to 50° C. The compression environment is not particularly limited, and the mixing environment of the solid electrolyte composition can be cited.

[0282] The compression process is preferably performed at least in the positive electrode active material layer, usually in the all-solid-state secondary battery precursor and in a state where no voltage is applied (no charge or discharge). In the present invention, no voltage is applied refers to a method of applying a voltage of 2.5 to 3.0 V equivalent to the end voltage of the initial discharge, in addition to a method of not applying any voltage to the positive electrode active material layer, etc.

[0283] The positive electrode active material layer is compressed until the porosity of the compressed positive electrode active material layer is less than the porosity of the positive electrode active material layer after charging. Ideally, the compression is performed until the voids from the negative electrode active material precursor are completely flattened (until the porosity of the positive electrode active material layer before charging is reached), but in practice, the compression is performed to a porosity close to that of the positive electrode active material layer before charging. For example, the compression is performed to a porosity that is 1.5% higher, preferably 1% higher, and more preferably 0.5% higher than the porosity of the positive electrode active material layer before charging.

[0284] From the viewpoint of compressing the positive electrode active material layer (squeezing the gaps), this compression process is different from the pressurization constraint preferably applied when using an all-solid-state secondary battery.

[0285] Generally, when manufacturing an all-solid-state secondary battery, the laminate (all-solid-state secondary battery precursor) further having a negative electrode active material layer is not pressurized at a pressure at which any layer is compressed by means of a positive electrode active material layer and a solid electrolyte layer and an all-solid-state secondary battery. This is because when there are gaps in the negative electrode active material layer and the positive electrode active material layer, cracks or cracks are generated in the solid electrolyte layer between the two layers, and the secondary battery cannot fully function.

[0286] However, in the manufacturing method of the present invention, since the process of compressing the positive electrode active material layer is performed after the charging process, voids from the negative electrode active material precursor are formed in the positive electrode active material layer of the compressed stack, and the voids in the negative electrode active material layer are almost not increased after the negative electrode active material layer is formed. In this way, the manufacturing method of the present invention, which sets the void amount for the positive electrode active material layer and the negative electrode active material layer and pressurizes the above-mentioned stack, can compress the positive electrode active material layer without generating cracks or cracks in the solid electrolyte layer. When the discharge process is not performed before the compression process (the charging process and the compression process are performed without intervening the discharge process), the generation of cracks in the solid electrolyte layer can be more effectively suppressed.

[0287] The compression process is performed in the above manner to produce an initially charged, preferably initialized, all-solid-state secondary battery. As described above, the all-solid-state secondary battery exhibits high battery capacity and high energy density.

[0288] Example

[0289] The present invention will be described in further detail below with reference to the Examples. The present invention is not limited thereto. In the following Examples, "parts" and "%" indicating the composition are by mass unless otherwise specified.

[0290] <Synthesis Example 1: Synthesis of Sulfide Inorganic Solid Electrolyte Li-PS Glass>

[0291] As a sulfide-based inorganic solid electrolyte, Li-PS-type glass was synthesized with reference to the non-patent literature of T. Ohtomo, A. Hayashi, M. Tatsumisago, Y. Tsuchida, S. Hama, K. Kawamoto, Journal of Power Sources, 233, (2013), pp231-235 and A. Hayashi, S. Hama, H. Morimoto, M. Tatsumisago, T. Minami, Chem. Lett., (2001), pp872-873.

[0292] Specifically, 2.42 g of lithium sulfide (Li 2 S, Aldrich. Inc., purity> 99.98%) and 3.90g phosphorus pentasulfide (P 2 S 5 , Aldrich. Inc., purity> 99%), and put it into an agate mortar and mixed it for 5 minutes using an agate milking stick. 2 S and P 2 S 5 The mixing ratio is Li in molar ratio. 2 S:P 2 S 5 =75:25.

[0293] 66 zirconia beads with a diameter of 5 mm were placed in a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), and the total amount of the mixture of the above-mentioned lithium sulfide and phosphorus pentasulfide was further placed, and the container was sealed under an argon atmosphere. The container was installed in a planetary ball mill P-7 (trade name) manufactured by Fritsch Co., Ltd., and mechanical grinding was performed at a temperature of 25°C and a rotation speed of 510 rpm for 20 hours to obtain 6.20 g of a yellow powder of sulfide inorganic solid electrolyte (Li-PS glass). The ion conductivity is 0.28 mS / cm. The particle size of the Li-PS glass based on the above-mentioned measurement method is 1 μm.

[0294] Example 1

[0295] In this example, an all-solid-state secondary battery having a positive electrode active material layer containing a negative electrode active material precursor and a Si negative electrode (negative electrode active material layer) was manufactured.

[0296] <Production of solid electrolyte sheets>

[0297] 100 mg of the synthesized sulfide inorganic solid electrolyte was placed in a cylinder with an inner diameter of 10 mm manufactured by Macor (registered trademark), and pressed for 1 minute at a pressure of 180 MPa under an argon atmosphere at 25° C. Thus, a solid electrolyte sheet composed of a sulfide inorganic solid electrolyte (thickness 600 μm) was obtained.

[0298] <Production of negative electrode sheet>

[0299] - Preparation of negative electrode composition -

[0300] Into a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), 66 zirconia beads with a diameter of 5 mm were placed, and 9.0 g of the Li-PS type glass synthesized in the above-mentioned Synthesis Example 1, 1.3 g of particles of modified polyvinylidene fluoride resin (PVDF) (4500-20 (trade name), manufactured by ARKEMA) as a binder, and 12 g of diisobutyl ketone as a dispersion medium were added. Then, the container was installed in a planetary ball mill P-7 (trade name, manufactured by Fritsch Co., Ltd.), and stirring was continued at a temperature of 25°C and a rotation speed of 300 rpm for 2 hours.

[0301] 9.0 g of Si powder (Silicon Powder, average particle size 1 to 5 μm based on the above-mentioned measurement method, manufactured by AlfaAesar) and 0.9 g of acetylene black as a conductive aid were further added, and 5 g of diisobutyl ketone was further added. The container was then mounted on a planetary ball mill P-7 (trade name, manufactured by Fritsch Co., Ltd.), and stirred at 150 rpm for 5 minutes at a temperature of 25° C. In this way, a negative electrode composition (slurry) was prepared.

[0302] -Film formation of negative electrode active material layer-

[0303] The prepared negative electrode composition was wet-coated on a copper foil having a thickness of 8 μm at a weight per unit area of ​​2 mg / diameter 10 mm, dried at 100° C., and temporarily pressed at 180 MPa to form a Si negative electrode active material layer.

[0304] In this way, a negative electrode sheet having a copper foil and a Si negative electrode active material layer (thickness 30 μm) was produced.

[0305] <Lamination of solid electrolyte sheet and negative electrode sheet>

[0306] The negative electrode sheet was stacked on the solid electrolyte sheet so that the Si negative electrode active material layer of the disc-shaped negative electrode sheet punched out from the produced negative electrode sheet into a disc shape with a diameter of 10 mm was in contact with the surface of the disc-shaped solid electrolyte sheet punched out from the solid electrolyte sheet into a disc shape with a diameter of 10 mm, and the pressure was set to 24 MPa in an argon environment at 25° C. and pressed for 1 minute. In this way, a negative electrode sheet stacked with a solid electrolyte layer was produced.

[0307] <Production of positive electrode sheet>

[0308] Next, a positive electrode sheet consisting of a positive electrode current collector and a positive electrode active material layer was prepared.

[0309] - Preparation of positive electrode composition -

[0310] 66 zirconia beads with a diameter of 5 mm were placed in a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), and 2.0 g of Li-PS glass synthesized in the above-mentioned synthesis example 1, 0.1 g of styrene butadiene rubber (product code 182907, manufactured by Aldrich) and 22 g of octane as a dispersion medium were placed. Then, the container was installed in a planetary ball mill P-7 manufactured by Fritsch Co., Ltd., and stirred at a temperature of 25°C and a speed of 300 rpm for 2 hours. Then, the positive electrode active material layer LiNi 0.85 Co 0.10 Al 0.05 O 2 (lithium nickel cobalt aluminum oxide) 7.11 g and Li as a precursor of the negative electrode active material 2 CO 3 0.79 g of lithium carbonate (average particle size 1 μm) was placed in a container, and the container was again mounted on a planetary ball mill P-7, and mixing was continued at 100 rpm for 15 minutes at 25° C. In this way, a positive electrode composition (slurry) containing a negative electrode active material precursor was obtained.

[0311] Next, the positive electrode composition obtained above was applied to an aluminum foil with a thickness of 20 μm as a current collector with a unit area weight of 15 mg / diameter 10 mm using a baking applicator, and heated at 80°C for 2 hours to dry the positive electrode composition. Then, a hot press was used to heat (120°C) the positive electrode composition dried to a specified density while applying pressure (600 MPa, 1 minute). In this way, a positive electrode sheet having an aluminum foil and a positive electrode active material layer (thickness 110 μm) was prepared.

[0312] <Manufacturing of all-solid-state secondary batteries>

[0313] -Production of laminated body-

[0314] By applying a liquid obtained by mixing a lithium-ion battery electrolyte with polyethylene oxide (PEO) on the surface of the solid electrolyte layer of the disc-shaped negative electrode sheet laminated with the solid electrolyte layer, the positive electrode active material layer of the disc-shaped positive electrode sheet punched out from the prepared positive electrode sheet into a disc shape with a diameter of 10 mm was attached. In this way, a disc-shaped laminate (all-solid-state secondary battery precursor) consisting of a Si negative electrode collector, a Si negative electrode active material layer, a solid electrolyte layer, a positive electrode active material layer and a positive electrode collector was obtained.

[0315] -Charging process (initial charging)-

[0316] The entire disk-shaped laminate was restrained in the stacking direction with a restraining pressure of 8 MPa and a current of 0.09 mA / cm 2 The initial charge was performed under the conditions of 4.2V, 4.2V voltage, 20 hours charging time and 25°C temperature. The lithium ions generated from the lithium carbonate by the initial charge were coated on the Si negative electrode active material layer as a lithium alloy, and the carbon dioxide gas was released outside the battery. The positive electrode active material layer after the initial charge was observed, and the result showed that the porosity (based on the above-mentioned measurement method) increased by 7% to 15% relative to the positive electrode active material layer before the initial charge.

[0317] -Compression process-

[0318] After the initial charge, the disc-shaped stack was freed from the constraints, and a pressure of 100 MPa was applied between the positive collector and the Si negative collector, and the disc-shaped stack after the initial charge was pressed in the stacking direction and the positive active material layer was compressed. The compression was performed for 1 hour at room temperature (25°C) and without applying voltage (charging and discharging) to the disc-shaped stack using a hot press.

[0319] The positive electrode active material layer was observed to be compressed (thinned) to a state where the porosity was increased by 1% compared to the positive electrode active material layer before initial charge (the porosity of 6% of the positive electrode active material layer before initial charge was compressed).

[0320] In this way, it is produced Figure 1 An all-solid-state secondary battery with the layer structure shown.

[0321] Comparative Example 1

[0322] An all-solid secondary battery was produced in the same manner as in Example 1 except that the pressure in the compression step was set to 8 MPa. The positive electrode active material layer in the all-solid secondary battery had a porosity of 7% and was not compressed (thinned) before and after the compression step.

[0323] Comparative Example 2

[0324] In this example, an all-solid-state secondary battery including a positive electrode active material layer not containing a negative electrode active material precursor and a Si negative electrode (Si negative electrode active material layer) was manufactured.

[0325] In the manufacturing method of the all-solid-state secondary battery of Example 1, the following positive electrode composition is used (the preparation of the positive electrode sheet is the same as that of Example 1), and an all-solid-state secondary battery having a positive electrode active material layer that does not contain a negative electrode active material precursor is manufactured in the same manner as the manufacturing method of the all-solid-state secondary battery of Example 1, except that the compression step is not performed.

[0326] - Preparation of positive electrode composition -

[0327] 66 zirconia beads with a diameter of 5 mm were placed in a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), and 2.0 g of Li-PS glass synthesized in the above-mentioned synthesis example 1, 0.1 g of styrene butadiene rubber (product code 182907, manufactured by Aldrich) and 22 g of octane as a dispersion medium were placed. Then, the container was installed in a planetary ball mill P-7 manufactured by Fritsch Co., Ltd., and stirred at a temperature of 25°C and a speed of 300 rpm for 2 hours. Then, the positive electrode active material layer LiNi 0.85 Co 0.10 Al 0.05 O 2 7.9 g of (lithium nickel cobalt aluminum oxide) was placed in a container, and the container was again mounted on a planetary ball mill P-7, and mixing was continued at a temperature of 25° C. and a rotation speed of 100 rpm for 15 minutes. In this way, a positive electrode composition was obtained.

[0328] <Evaluation: Charge and discharge cycle characteristics test>

[0329] Before the charge-discharge cycle characteristic test, each of the above-fabricated all-solid-state secondary batteries was constrained in the stacking direction at a constraining pressure of 8 MPa and at a current of 0.09 mA / cm 2 The battery was initialized by initial discharge under the conditions of 2.5 V end voltage, 18 hours charging time and 25° C. temperature.

[0330] Next, each of the all-solid-state secondary batteries was used to perform (rapid) charge and discharge under the following conditions to conduct a charge and discharge cycle characteristic test (harsh accelerated conditions).

[0331] (condition)

[0332] At 2.2 mA / cm 2The current density was charged to 4.25 V and the 2 A charge-discharge cycle in which the battery was discharged to 2.5 V at a current density of 1.5 V was defined as one cycle, and this was repeated 7 times.

[0333] The charge capacity and discharge capacity were measured every cycle, and the charge and discharge efficiency was calculated from the following formula to evaluate the charge and discharge cycle characteristics.

[0334] Formula: Charge and discharge efficiency (%) = [discharge capacity / charge capacity] × 100

[0335] The results of the charge and discharge cycle characteristics test are shown below.

[0336] Example 1

[0337] Regarding the all-solid-state secondary battery of Example 1, the discharge capacity of 7 cycles is equal to that of Comparative Example 2 (the same as the unit area weight of the positive electrode active material layer) using 7.9g of positive electrode active material NCA. Thus, it is confirmed that the all-solid-state secondary battery shows a discharge capacity equal to that of Comparative Example 2, and the battery volume is reduced by thinning the positive electrode active material layer, and the volume energy density is improved.

[0338] Moreover, the charge-discharge efficiency of 7 cycles was stabilized at 99%. Thus, it can be seen that the generation of short circuit can be suppressed. Moreover, the interface peeling of the negative electrode active material layer and the solid electrolyte layer caused by the volume expansion and contraction of the negative electrode active material layer can be prevented, and a high discharge capacity can be maintained.

[0339] The cross-section of the solid electrolyte layer was subjected to ion beam milling and then observed using a SEM. As a result, no cracks or fissures were confirmed.

[0340] Comparative Example 1

[0341] Since the positive electrode active material layer of the all-solid-state secondary battery of Comparative Example 1 was not compressed, no improvement in volume energy density was observed.

[0342] Comparative Example 2

[0343] Since the positive electrode active material layer of the all-solid-state secondary battery of Comparative Example 2 does not contain a negative electrode active material precursor, it is not possible to compensate for the reduction in the amount of lithium metal in the Si negative electrode active material layer, and the discharge capacity is insufficient. In addition, since the thickness of the positive electrode active material layer is constant (unchanged), the increase in volume energy density is not confirmed.

[0344] The present invention has been described together with its embodiments. The inventors believe that unless otherwise specified, the present invention is not limited in any details of the description and should be broadly interpreted as long as it does not violate the spirit and scope of the invention shown in the attached claims.

[0345] This application claims priority based on Japanese Patent Application No. 2019-060215 filed in Japan on March 27, 2019, which are hereby incorporated by reference, and the contents thereof are incorporated into this specification as a part of what is described in this specification.

[0346] Explanation of symbols

[0347] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state secondary battery.

Claims

1. A method for manufacturing an all-solid-state secondary battery, the all-solid-state secondary battery comprising: a solid electrolyte layer containing an inorganic solid electrolyte and a positive electrode active material layer on one surface of the solid electrolyte layer, The method for manufacturing the all-solid-state secondary battery comprises: A step of forming a positive electrode active material layer on one surface of the solid electrolyte layer using a positive electrode composition containing a positive electrode active material and a negative electrode active material precursor; A charging step of charging a stack including the positive electrode active material layer and the solid electrolyte layer while the stack is constrained in a stacking direction at a pressure of 0.05 MPa or more and less than 10 MPa; and After the charging step, a compression step of compressing at least the positive electrode active material layer by applying pressure, in, In the step of compressing, the stacked body is pressurized at a pressure of 80 to 1000 MPa.

2. The method for manufacturing an all-solid-state secondary battery according to claim 1, wherein: After the compression step, a discharge step of discharging at least the laminated body in which the positive electrode active material layer is compressed is further included.

3. The method for manufacturing an all-solid-state secondary battery according to claim 1, wherein: The compressing step is performed without applying a voltage to the stacked body.

4. The method for manufacturing an all-solid-state secondary battery according to claim 1, wherein: The negative electrode active material precursor is at least one compound selected from carbonates, oxides and hydroxides of alkali metals or alkaline earth metals.

5. The method for manufacturing an all-solid-state secondary battery according to claim 1, wherein: The all-solid-state secondary battery includes a negative electrode active material layer on the other surface of the solid electrolyte layer.

6. The method for manufacturing an all-solid-state secondary battery according to claim 5, wherein: Prior to the charging step, a step of forming the negative electrode active material layer using a negative electrode composition containing silicon or an alloy containing silicon is provided. 7 . An all-solid-state secondary battery obtained by using the method for manufacturing an all-solid-state secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Latex agglutination reaction measuring instrument

    JP1987022066A

  • Elastic gripping pawl for sheet rotary press

    JP1987051452A

  • Catalyst carrier and production thereof

    JP1990006856A

  • Four-wheel steering device

    JP1991045473A

  • Distortion compensator

    JP1993090844A